Focusing on the Customer How Boeing Does It - Condit, Philip M.
Philip M. Condit reviews the lessons Boeing has learned from making its airline customers full partners in the improved design-build process for its newest jetliner.
Success in the marketplace depends upon designing and building products that provide the best solution to customers' changing needs.
In today's competitive environment, companies need a thorough understanding of their customers to drive research and development. The process should be customer-driven, not technology-driven. In developing Boeing's newest jetliner, the 777, the company has made its airline customers full partners in the design-build process. Design-build teams also include suppliers and various disciplines within the company, such as finance, operations, engineering design, manufacturing and customer support. While there are enormous benefits to this teaming strategy, the process of building effective teams is difficult. Many cultural and organizational barriers prevent people from working together effectively.